Antiplasmin Deficiency in Polycythaemia: a Form of Thrombopathy - de Vries, S. I; Braat-van Straaten, M. A. J; Müller, E; Wettermark, M (Thrombosis and Haemostasis, 1961)
A marked fibrinolytic activity could be demonstrated in the blood of 10 patients with polycythaemia. In these cases fibrinolysis was considered the result of a deficiency an antiplasmin. It could be demonstrated that this naturally occurring inhibitor of fibrinolysis is present in normal platelets but is lacking in the patient’s own thrombocytes. This factor is probably attached to the surface of the thrombocytes. It could be removed by repeatedly washing. Lack of antiplasmin is a dysfunction of platelets and a form of thrombopathy. It does not respond on treatment with ACA or prednisone. In primary polycythaemia busulfan (Myleran) was considered to be the treatment of choice, whereas in 1 case of secundary erythrocytosis (Fallot’s tetralogy) the reaction on unroasted peanuts was unmistakable. In 4 more patients an alcoholic extract of peanuts was given, and promising results were obtained in 3 of them. The importance of this “thrombopathic type’ of fibrinolysis has been pointed out especially in view of surgical interventions.